Identification of KIR3DL1*0200101 by long-range sequence-based techniques. - Yindom, L; Wang, L; Dong, T; Rowland-Jones, S (2014)
The new KIR3DL1*0200101 differs from KIR3DL1*01502 with 12 single nucleotide polymorphisms (SNPs) in two exons and seven introns.